A functional evaluation of the spatiotemporal patterns of temperature change in India. (22nd June 2017) - Narula, Pankaj; Sarkar, Kaustav; Azad, Sarita
ABSTRACT: The present endeavour aims to identify the spatiotemporal footprints of temperature change in India by analysing monthly temperature data pertaining to the period of 1901–2005. Functional data analysis (FDA) has been implemented for detecting the temporal manifestation of mean change years. The estimated change years have been observed to largely pertain to the latter half of 20th century and to fall in close proximity to the previously reported global change years 1963 and 1976. Large portions of the Indian mainland have been observed to exhibit significant temperature changes after approximately every 12 years since 1940. The all‐India temperature rise is estimated to be 0.53 °C during 1901–2005. It has also been observed that, temperature rise has primarily occurred during post‐monsoon and winter seasons. An index, consolidating the results of FDA such as change years and temperature rise, has been developed to quantify temperature‐change severity. Based on the spatial distribution of index values, the hot‐spots have been found to cluster over the north‐central and eastern parts of the country. Abstract : The spatiotemporal footprints of temperature change in India has been studied using functional data analysis (FDA) over the period of 1901–2005. The estimated change years fall in close proximity to the previously reported global change years 1963 and 1976. Large portions of the Indian mainland have been observed to exhibit significant temperature changes after approximately every 12 years since 1940. An index, consolidating the results of FDA, has been developed to quantify temperature change severity .